2016
DOI: 10.1111/bjh.14057
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibition improves anaemia and reduces organ damage in a murine model of sickle cell disease

Abstract: Summary Mechanistic target of rapamycin (mTOR) has been shown to play an important role in red blood cell physiology, with inhibition of mTOR signalling leading to alterations in erythropoiesis. To determine if mTOR inhibition would improve anaemia in sickle cell disease (SCD), mice with SCD were treated with the dual mTORC1/2 inhibitor, INK128. 1 week after daily oral drug treatment, erythrocyte count, haemoglobin, and haematocrit were all significantly increased while reticulocyte counts were reduced. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…We next tested whether Rapamycin, a known mTOR inhibitor, may modulate Fyn −/− mouse erythropoiesis as reported for other models of pathologic erythropoiesis. 37,38,42,47 In Fyn −/− mice, Rapamycin administration reduced total erythroblasts, while no significant effects were observed in control animals as previously reported 37,38,42,47 (Figure 4A). (Figure 4B, C).…”
Section: The Mtor Inhibitor Rapamycin Unblocks Autophagy Defect Andsupporting
confidence: 83%
“…We next tested whether Rapamycin, a known mTOR inhibitor, may modulate Fyn −/− mouse erythropoiesis as reported for other models of pathologic erythropoiesis. 37,38,42,47 In Fyn −/− mice, Rapamycin administration reduced total erythroblasts, while no significant effects were observed in control animals as previously reported 37,38,42,47 (Figure 4A). (Figure 4B, C).…”
Section: The Mtor Inhibitor Rapamycin Unblocks Autophagy Defect Andsupporting
confidence: 83%
“…We next tested whether Rapamycin, a known mTOR inhibitor, may modulate Fyn -/mouse erythropoiesis as reported for other models of pathologic erythropoiesis. 35,36,40,45 In Fyn -/mice, Rapamycin administration reduced total erythroblasts, while no significant effects were observed in control animals as previously reported 35,36,40,45 (Figure 5d). In Fyn -/mice treated with Rapamycin, this was associated with amelioration of the terminal phase of erythropoiesis ( Figure 6Sc).…”
Section: The Mtor Inhibitor Rapamycin Unblocks Autophagy Defect and Asupporting
confidence: 84%
“…The inhibition of mTOR by Sirolimus has been shown to promote autophagy of mitochondria in human cell hybrid lines carrying pathological mitochondrial DNA mutations. (29) mTOR inhibition has also recently been shown to improve anemia and reduce organ damage in a murine model of SCD(14). In baboons ( P. anubis ), ChIP analysis showed that RN-1 increased the levels of activating chromatin marks (H3K4Me2, H3K4Me3 and H3K9ac) associated with the γ-globin, but not the ε-globin which suggests a specific effect of the drug on γ-globin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we show that RBCs with mitochondria are associated with high levels of ROS accumulation. Finally, we demonstrate that two preclinical candidate drugs, the LSD1 inhibitor, RN-1(12, 13) and mTOR inhibitor(14), Sirolimus, both reduce levels of mitochondria retaining RBCs in a SCD mouse model.…”
Section: Introductionmentioning
confidence: 85%